Pengaruh Tekanan Kompaksi Terhadap Densitas Dan Kekerasan AMC Diperkuat SiC Dan RHA Metode Metalurgi Serbuk - Febriany, Sulis; Sukanto, Sukanto; Subkhan, Subkhan (Jurnal Inovasi Teknologi Terapan, 2024)
In the current era, the automotive industry is growing rapidly, one of which is in the field of transportation in the manufacture of brake linings. Generally, brake linings are made of materials containing asbestos which endanger health. Therefore, a material innovation is needed to replace the role of asbestos such as aluminum matrix composites. The purpose of this study was to determine the effect of different hot compaction pressures on the density and hardness of AMC reinforced with SiC and RHA. The method used in this research is powder metallurgy method, which consists of preparation, mechanical mixing, compacting, and sintering stages. The mixing process uses a ball mill machine with ball ratio parameters of 10:1 and stirring time for 2 hours and with a rotating speed of 90 rpm. The compacting process is done by two-way pressing from a hydraulic press machine with a pressure gauge. In this process the parameters used are 5600 PSi, 6000 Psi and 6400 Psi pressure with a holding time of 15 minutes. Density testing was done with ASTM B962-17 according to Archimedes' law. Hardness testing using ASTM E110-14 with a portable brinell hardness tester. The test results show that the higher the compaction pressure, the higher the density and hardness values. With the highest density value of 1.69 g/mm3 and the highest hardness value of 39.33 HB for specimens with 6400 Psi compaction pressure parameters.